Targeted screening of 11 bisphenols and 7 plasticizers in food composites from Canada and South Africa. (15th August 2022) - Tian, Lei; Zheng, Jingyun; Pineda, Marco; Yargeau, Viviane; Furlong, Daniel; Chevrier, Jonathan; Bornman, Riana; Obida, Muvhulawa; Gates Goodyer, Cindy; Bayen, Stéphane
Highlights: 18 contaminants were analyzed in 168 food from Canada and South Africa. Bisphenol A (BPA), bisphenol S (BPS) and seven plasticizers were detected in food. DBP and DEP were the most frequently detected contaminants in Montreal. DINP was the most frequently detected contaminant in South Africa. DEHA levels in packaged fish were higher than the values for non-packaged fish. Abstract: A sensitive method based on ultrasound-assisted liquid extraction coupled with liquid chromatography was applied to screen 18 plastic-related contaminants in 168 food composites (namely fish fillets, chicken breast, canned tuna, leafy vegetables, bread and butter) collected in Montreal (Canada), Pretoria and Vhembe (South Africa). Bisphenol A (BPA), bisphenol S (BPS) and seven plasticizers (di- n -butyl phthalate (DBP), diethyl phthalate (DEP), (2-ethylhexyl) phthalate (DEHP), di-(2-ethylhexyl) adipate (DEHA), di-isononyl phthalate (DINP), di-(isononyl)-cyclohexane-1, 2-dicarboxylate (DINCH)) were detected in different foods from both countries. DBP and DEP were the most frequently detected contaminants in food collected in Montreal (75% for both) and DINP was the most frequently detected contaminant in food from South Africa (67%). DEHA concentration in packaged fish were significantly higher than the values for non-packaged fish ( p < 0.01) suggesting that the packaging film can be one source of DEHA in fish.